Practical forming die design and manufacture for sheet metal stainless steel precision parts - Cheung, Thomas Wing Lau. (2009)
This project deals with precision stainless steel sheet metal forming which produces parts in the regime of near net shape. The stamping parts concerned are backs for watches which can be of various profiles and sizes.